Systematic Review of Total Wrist Arthroplasty and Arthrodesis in Wrist Arthritis - Berber, Onur; Garagnani, Lorenzo; Gidwani, Sam (Journal of Wrist Surgery, 2018)
Background End-stage wrist arthritis has traditionally been treated with a total wrist fusion. There is a recent trend toward motion preserving surgery in the form of total wrist replacement.Questions Is there a functional benefit to performing a total wrist replacement instead of a total wrist fusion in patients with end-stage wrist arthritis? Is there any difference in secondary outcome measures including pain, grip strength, and range of motion? Does the risk of adverse events and treatment failure differ between the two techniques?Methods A systematic literature search was performed to identify studies reporting either total wrist arthrodesis or arthroplasty for end-stage wrist arthritis. Studies were systematically screened and assessed for risk of bias and quality. Data were extracted and reviewed.Results A total of 43 studies were included in the review: 17 on arthrodesis, 24 on arthroplasty, and 2 matched cohort studies. This represented 669 index arthrodesis operations in 603 patients, and 1,371 index arthroplasty operations in 1,295 patients. A significant improvement in functional outcome was seen with both interventions. Similar improvements were seen in pain scores, and modest improvements were seen in grip strength. Range of motion following arthroplasty improved to a functional level in two studies. Complication rates were higher after arthroplasty (range: 0.2–9.5%) than those after arthrodesis (range: 0.1–6.1%; p = 0.06). Fourth-generation implants (range 0.1–2.9%) performed better than earlier designs (range: 0.2–8.1%; p = 0.002). Implant revision rates ranged from 3.5 to 52.6%. Fourth-generation prostheses survival rates were 78% at 15 years (Universal 2), 86% at 10 years (Motec), 90% at 9 years (Re-Motion), and 95% at 8 years (Maestro).Conclusion The newer fourth-generation wrist implants appear to be performing better than earlier designs. Both wrist arthrodesis and wrist arthroplasty improve function, pain, and grip strength. The risk of complication following wrist replacements is higher than that after total wrist arthrodesis.
Keywords: wrist; arthritis; arthroplasty; arthrodesis; systematic review